Changing of viscosity and thermal properties of olive oil with different harvesting methods and waiting period - Sağlam, Cihangir (Array, 2018)
The aim of this paper is to determine how different harvesting methods of olives and the waiting period before the extraction of the extra virgin olive oil affect the viscosity and some thermal properties, namely thermal conductivity and thermal resistivity. Olive trees in the Aegean region of the western part of Turkey were harvested by using six different harvesting methods: by hand, harvesting by a beating pole on a synthetic fabric, harvesting by a beating pole on a platform, harvesting by machine on a synthetic fabric, harvesting by machine on a platform and direct collecting of dropped olives by hand. Olive oil samples were obtained in certain intervals between the harvesting and processing that was made by using a laboratory type system. The viscosity values of oil samples were measured by using a vibro-viscometer. The thermal conductivity and thermal resistivity of oil samples were measured simultaneously by using the KD2 Thermal properties analyzer. As a result, viscosity, thermal conductivity and thermal resistivity values changed related to the harvesting method and the waiting period after harvesting to obtain olive oil. While viscosity (dynamic) and thermal conductivity values increased with the increase of the waiting time, thermal resistivity values decreased. The lowest viscosity and thermal conductivity values and the highest resistivity values were found for oils that were obtained from olives harvested by hand.